Melihat Palu-Donggala dari Angkasa: Modal Sosial dan Pemulihan Ekonomi Pascagempa - Wahyuni, Wira; Dartanto, Teguh (Future Science, 2024)
This study aims to analyze the relations of social capital (“gotong royong”, the existence of sporting activities, the number of activities car-ried out by the Badan Permusyawaratan Desa) on the earthquake fol-lowed by tsunami and liquefaction disaster recovery process that oc-curred in Central Sulawesi on September, 26th 2018. By using the intensi-ty of the night light (Suomi National Polar Partnership Visible Infrared Imaging Radiometer Suite – SNPP VIIRS data) in assessing the time for recovery of economic activity and PODES 2018, a survival analysis was performed. The analysis shows that villages with higher social capital need a shorter time to reach their pre-disaster recovery. The chances of a village affected by the disaster having sports activities were 13,046 times faster than that of villages without sports activities. This research also indicates the positive role of village institutions and infrastructure in accelerating the recovery process of villages affected by disasters.